Predicting the National Football League potential of college quarterbacks - Niven Winchester; J. Dean Craig (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2020)
We use college football data and, in some cases, ESPN scout grades to estimate (1) attributes that are likely to result in a college quarterback being selected by a National Football League (NFL) team, and (2) the performance of rookie quarterbacks in the NFL. We find that both college passing and rushing ability are significantly correlated with NFL selection, with strong passing ability the most important trait for making the NFL. Among quarterbacks selected for the NFL, college rushing ability is significantly correlated with NFL performance, but college passing ability is not. College rushing ability is also a significant determinant of NFL performance when scout grades are included as an explanatory variable. We conclude that rushing prowess is the key determinant of the NFL success of quarterbacks with sufficient passing skills to warrant NFL selection. Our findings also indicate that scouts systematically undervalue rushing ability when assessing the NFL potential of college quarterbacks.
Keywords: 330; OR in sports; Selection; Multivariate regression analysis